2016
DOI: 10.2147/ijn.s113375
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of TiO<sub>2</sub> nanoporous modification and platelet-rich plasma treatment on titanium-implant stability in ovariectomized rats

Abstract: For several decades, titanium and its alloys have been commonly utilized for endosseous implantable materials, because of their good mechanical properties, chemical resistance, and biocompatibility. But associated low bone mass, wear and loss characteristics, and high coefficients of friction have limited their long-term stable performance, especially in certain abnormal bone-metabolism conditions, such as postmenopausal osteoporosis. In this study, we investigated the effects of platelet-rich plasma (PRP) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Analyzes of bone mineralization evolution were performed by histological analysis 45 days after implantation [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Analyzes of bone mineralization evolution were performed by histological analysis 45 days after implantation [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, multiple growth factors, most commonly, platelet-derived growth factors have been utilized for enhancing the BIC [ 20 ]. Some studies have shown improved implant stability and earlier osteogenesis with plasma containing higher concentration of platelets [ 21 , 22 ]. However, there is lack of evidence related to the influence of different platelet-derived plasma concentrations on the 3D BIC at follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of platelet concentrates for the treatment and management of osteoporosis (Tables 2 and 3 ) [ 21 – 23 , 37 , 56 – 64 ]. All studies were conducted on ovariectomized (OVX) animal models including mice [ 22 , 23 , 37 , 56 ], rats [ 21 , 57 – 60 , 62 , 64 ], and rabbits [ 61 , 63 ].…”
Section: Role Of Pdbs In Osteoporosismentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of platelet concentrates for the treatment and management of osteoporosis (Tables 2 and 3 ) [ 21 – 23 , 37 , 56 – 64 ]. All studies were conducted on ovariectomized (OVX) animal models including mice [ 22 , 23 , 37 , 56 ], rats [ 21 , 57 – 60 , 62 , 64 ], and rabbits [ 61 , 63 ]. In these studies, the systemic and localized application of platelet concentrates (PRP or PRF) alone or in combination with osteoinductive and osteoconductive biomaterials has been investigated [ 21 , 37 , 57 , 58 , 60 – 64 ].…”
Section: Role Of Pdbs In Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation